Evaluation of a New Scoring System for Retinal Nerve Fiber Layer Photography Using HRA1 in 964 Eyes - Hong, Samin; Moon, Jong Wook; Ha, Seung Joo; Kim, Chan Yun; Seong, Gong Je; Hong, Young Jae (Korean journal of ophthalmology, 2007)
To evaluate retinal nerve fiber layer (RNFL) defect by a new scoring system for RNFL photography using the Heidelberg Retina Angiograph 1 (HRA1). This retrospective study included 128 healthy eyes and 836 primary open-angle glaucoma eyes. The RNFL photography using HRA1 was interpreted using a new scoring system, and correlated with visual field indices of standard automated perimetry (SAP). Using the presence of RNFL defect, darkness, width, and location, we established the new scoring system of RNFL photos. The mean RNFL defect score I in the early, moderate, severe, and control groups were 7.3, 9.2, 10.4, and 3.6, respectively. The mean RNFL defect score II in the early, moderate, severe, and control groups were 14.5, 28.5, 43.4, and 3.4, respectively. Correlations between the RNFL defect score II and the mean deviation of SAP was the strongest of the various combinations (r=-0.675, P<.001). Using a new scoring system, we propose a method for semi-quantitative interpretation of RNFL photographs. This scoring system may be helpful to distinguish between normal and glaucomatous eyes, and the score is associated with the severity of visual field loss.